0427 Having Insomnia vs. Identifying as an "Insomniac": What is the role of insomnia severity?. (25th May 2022) - Boyle, Julia; Muench, Alexandria; Thompson, Michelle; Seewald, Mark; Vargas, Ivan; Perlis, Michael
Abstract: Introduction: The present study sought to evaluate whether insomnia severity (i.e., sleep continuity disturbance) is worse in those who endorse insomnia identity (i.e., identify as an "insomniac") vs. those who endorse "having insomnia." Methods: This study utilized a cross-sectional group design in an archival/community dataset that was collected in the Philadelphia area. This dataset (n=3, 483) was comprised of adults between 18 and 90 years of age (X̅age=53.6±11.0; female [76.4%]; White [91.4%]). All subjects in this analysis endorsed sleep problems. Subjects answered questions regarding demographics, sleep continuity (in minutes), and insomnia identity ("Do you think of yourself as someone that has insomnia" and "do you think of yourself as an 'insomniac'"?). For both questions, individuals were categorized by their answers: strongly agree, agree, undecided, disagree, strongly disagree. MANOVAs and two-way ANOVAs were conducted to assess group differences (α=.01). Results: Most individuals endorsed "having insomnia" (n=2, 301 [66.1%; strongly agree and agree]) but did NOT endorse being an 'insomniac' (n=1, 981 [56.9%; undecided, disagree, and strongly disagree]). For all measures, except TST, the two groups did not differ with respect to insomnia severity (i.e., SL[55.4±48.5;60.5±52.1], WASO[45.1±51.7;47.6±55.3], EMA[71.8±51.6;72.9±52.4], and TST [328±75.5;319.6±76.4, p=.009]). The magnitude of the differences between these groups ranged from 1-10 minutes. Conclusion: It was found that individuals are more likely to endorse 'having insomnia' than they are to endorse being an 'insomniac.' Despite the implicit differences in "having" something vs. "being" something, the groups did not differ appreciably with respect to sleep continuity. Thus, the tendency to have insomnia identity may not be related to insomnia severity considerations. It is possible, if not likely, that such differences may be related to frequency or chronicity of insomnia. Barring, or in addition to these things, insomnia identity may be related to the mismatch between sleep ability and need and/or related to other non-specific factors. Future directions include refining the group definitions to include forms of insomnia identity that occur with relatively normal sleep continuity (i.e., normal severity and/or frequency and/or chronicity). It will also be important to evaluate whether the various forms of insomnia identity vary with age, sex, or disease comorbidity. Support (If Any): K24AG055602